Personal Values and Personalities: Positive Organizational Perspective on Political Skill of Indonesian Civil Apparatus (A Study in State Civil Apparatus in Indonesia) - Theresia Dewi Setyorini; Hendriati Agustiani; Marina Sulastiana; Zainal Abidin (UIN Sunan Kalijaga, 2021)
This study examines the role of personal values and personality in shaping important behaviors in the world of work. In the perspective of positive psychology, personal values and personality play a role in how people behave and make decisions. In this case, political skill is studied in a positive perspective as an important factor that affects the world of work, mainly in bureaucratic organizations. This study is a quantitative research using data collection scale. Three scales are used, namely Political Skill Inventory, Portrait of Personal Values, and Big Five Inventory. The research subjects were 406 State Civil Apparatus. The results of the study prove that the hypotheses which state that personal values and personalities are positively correlated with political skill are accepted. The conclusion shows that openness to change, as well as positive personality types are correlated with political skill. Meanwhile, neuroticism has a negative correlation with political skill. Thus, it can be concluded that a positive personality background and the value of openness affect a one’s political skill. A person who has positive personal and personality values has better political skill.Keywords: personal values, personality, political skill Studi ini meneliti peran personal values dan kepribadian dalam membentuk perilaku yang penting dalam dunia kerja. Berangkat dari sudut pandang psikologi positif, nilai personal dan kepribadian berperan terhadap bagaimana seseorang bersikap, berperilaku, dan mengambil keputusan. Dalam hal ini political skill dikaji dalam perspektif positif sebagai faktor penting yang berpengaruh dalam dunia kerja secara khusus di organisasi birokrasi. Penelitian ini merupakan penelitian kuantitatif yang pengumpulan datanya menggunakan skala. Tiga skala digunakan yaitu Political Skill Inventory, Portrait of Personal Values, dan Big Five Inventory. Subjek penelitian adalah Aparatur Sipil Negara yang berjumlah 406. Hasil penelitian membuktikan bahwa hipotesis yang menyatakan personal values dan kepribadian berkorelasi positif dengan political skill dinyatakan diterima. Kesimpulan menunjukkan bahwa openness to change, serta tipe kepribadian positif berkorelasi dengan political skill. Sedangkan neuroticism berkorelasi negative dengan political skill. Dengan demikian, dapat disimpulkan bahwa latar belakang kepribadian yang positif dan nilai keterbukaan mempengaruhi political skill seseorang. Seseorang yang memiliki nilai-nilai pribadi dan kepribadian positif memiliki political skill yang lebih baikKata kunci.: nilai-nilai pribadi, kepribadian, keterampilan politik